Doses de nitrogênio em cobertura no feijoeiro em sucessão a gramíneas no cultivo de inverno-primavera - Amaral, Camila Baptista do [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The common bean has been explored in different management systems, with emphasis on no-tillage system, since it presents interesting agronomic and commercial characteristics. In tropical regions, however, the greatest difficulty for success in this system is the maintenance of the straw, because of the high rate of decomposition in these regions. For this reason, species of high C/N ratio are the most suitable to render the management system with the common bean, such as corn and brachiaria. However, more attention should be given to nitrogen fertilization, due immobilization process that can occur in no-tillage system. Thus, the aim of this study was to evaluate the influence of topdressed nitrogen fertilization on the irrigated common bean in succession with maize and brachiaria, in single or intercropped grown, under no-tillage system. The experiment was conducted in eutrophic red latosol, loam texture, in split plot design with three replications. The plots consisted of: M + F) exclusive maize in summer and common bean in winter - spring, MB + F ) of maize intercropped with brachiaria in summer and common bean in winter - spring and B + F ) exclusive brachiaria in summer and common bean winter - spring. The subplots consisted of four topdressed rates of nitrogen, corresponding to 40, 80, 120 and 160 kg ha-1 of N and a witness that was omitted the nitrogen fertilization. Agronomic characteristics of maize (exclusive and intercropped) were evaluated, such as characteristics of the straw of the predecessor crop and agronomic and technological quality of the common bean crop. Intercropped brachiaria does not affect the characteristics of maize, compared to exclusive grown. When grown after brachiaria, the common bean have the highest yield (exclusive brachiaria bean in summer and in winter - spring). In all management systems, 136 kg ha-1 of nitrogen gave the maximum yield, mainly influenced by ...

O feijoeiro vem sendo explorado em diversos sistemas de produção, com grande destaque no plantio direto, uma vez que apresenta características agronômicas e comerciais interessantes para esse sistema. Em regiões tropicais, contudo, a maior dificuldade para se obter sucesso neste sistema está na manutenção da palhada, em razão da alta taxa de decomposição nestas regiões. Por este motivo, espécies de alta relação C/N são as mais indicadas para compor o sistema de produção junto ao feijoeiro, a exemplo do milho e da braquiária. Todavia, maior atenção deve ser dada à adubação nitrogenada, uma vez que pode ocorrer imobilização do nitrogênio, que é o elemento requerido em maior quantidade pelo feijoeiro. Desta forma, o objetivo deste trabalho foi avaliar a influência da adubação nitrogenada em cobertura no feijoeiro em sucessão à milho e braquiária, em cultivo exclusivo ou em consórcio, no quinto ano de implantação do sistema plantio direto. O experimento foi conduzido em um Latossolo Vermelho eutroférrico, textura argilosa, em blocos ao acaso no esquema de parcelas subdivididas, com três repetições. As parcelas foram constituídas de: M+F) cultivo de milho exclusivo no verão e do feijoeiro no inverno-primavera, MB+F) de milho consorciado com braquiária no verão e feijoeiro no inverno-primavera e B+F) braquiária exclusiva no verão e feijoeiro no invernoprimavera. As subparcelas foram constituídas de quatro doses de nitrogênio aplicado em cobertura no feijoeiro, correspondendo a 40, 80, 120 e 160 kg ha-1 de N e uma testemunha onde se omitiu o nutriente via adubação de cobertura. Foram avaliadas as características agronômicas do milho (exclusivo e em consórcio), características da palhada das culturas antecessoras ao feijoeiro e características agronômicas e qualidade tecnológica do feijoeiro. O cultivo de milho consorciado com braquiária não afeta ...
Keywords: Feijão comum; Feijão - Adubação; Fertilizantes nitrogenados; Milho; Gramínea; Beans